2015
DOI: 10.3389/fnagi.2015.00097
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Use Proprioception Rather than Visual and Vestibular Cues for Postural Motor Control

Abstract: Multiple factors have been proposed to contribute to the deficits of postural control in the elderly. They were summarized as sensory, motor, and higher-level adaptation deficits. Using a model-based approach, we aimed to identify which of these deficits mainly determine age-related changes in postural control. We analyzed postural control of 20 healthy elderly people with a mean age of 74 years. The findings were compared to data from 19 healthy young volunteers (mean age 28 years) and 16 healthy middle-aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
103
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 81 publications
10
103
2
2
Order By: Relevance
“…One factor in balance dysfunction may be changes in the robustness of peripheral vestibular signaling in the elderly (11). Another factor may be changes in how sensory information is processed by central circuits, as exemplified by a study which found that compared with younger subjects, the elderly favor the use of proprioceptive rather than visual and vestibular cues for postural motor control (12). Overall, there is an age-related decline of peripheral vestibular sensing and the central combination of different sensory signals for balance.…”
Section: Introductionmentioning
confidence: 99%
“…One factor in balance dysfunction may be changes in the robustness of peripheral vestibular signaling in the elderly (11). Another factor may be changes in how sensory information is processed by central circuits, as exemplified by a study which found that compared with younger subjects, the elderly favor the use of proprioceptive rather than visual and vestibular cues for postural motor control (12). Overall, there is an age-related decline of peripheral vestibular sensing and the central combination of different sensory signals for balance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate, however, that performance on the SEBT is expected to be fairly consistent between men and women when the reach distance has been normalized to leg length [25]. Also, while changes in postural control in the elderly are well documented [26], they are less established for young adults and middle-aged adults [27]. Yet Bouillon and Baker [28] found differences in reach distance on the SEBT between young and middle-age recreationally active women but our study was not powered to test for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory adaptation causes sensitivity adjustment which adapts to the recent perception experience (Webster 2012;Roseboom et al 2015). Sensory changes occur if there is undue impairment on the sensory system, or a change in human weight (Skrandies and Zschieschang 2015), or most commonly when the sensitivity declines due to ageing (Wiesmeier et al 2015;Humes 2015). Multisensory integration, acts as a fusion of sensory data, helps increase the accuracy of perception but the application is normally restricted to adults since the development of sensor fusion for humans only starts in preteen years (Nardini et al 2010).…”
Section: Duis For Human Inputsmentioning
confidence: 99%